The role of probiotics in improving the symptoms of irritable bowel syndrome - منهل نبيل يوسف, (Latakia University Journal -Medical Sciences Series, 2021)
Background: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder characterized by chronic abdominal pain and altered bowel habits without identifiable organic pathology. Growing evidence indicates that gut microbiota dysbiosis contributes to its pathophysiology, making probiotics a promising adjunctive therapy. Objective: To evaluate the effect of a multi-strain probiotic blend on symptom severity and quality of life in patients with IBS diagnosed according to Rome III criteria. Methods: In this randomized, double-blind, placebo-controlled trial, 61 IBS patients were randomized to receive either probiotic capsules (10 strains, 2.5×10^9 CFU per capsule) twice daily for 50 days or matching placebo. Symptom severity (IBS‑SSS) was assessed at baseline and every 10 days, and quality of life (IBS‑QOL) was evaluated at baseline and day 50. Results: Mean IBS‑SSS scores decreased significantly in the probiotic group from 271.0 ± 2.71 to 163.0 ± 4.08 (p<0.01), compared with a non-significant decrease in the placebo group from 268.0 ± 2.68 to 244.0 ± 2.76. IBS‑QOL scores improved in the probiotic group from 70.29 ± 0.92 to 74.95 ± 1.12 (p<0.05), while no significant change was observed in the placebo group. Conclusion: The multi-strain probiotic blend notably reduced IBS symptom severity and improved quality of life over 50 days, supporting its role as a safe and effective adjunctive therapy. Longer-term trials with larger sample sizes are warranted to confirm sustainability of effects and elucidate underlying mechanisms.